1998
DOI: 10.1136/sti.74.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction detection of Haemophilus ducreyi DNA

Abstract: Objectives: To develop a polymerase chain reaction (PCR) method to detect Haemophilus ducreyi DNA in cultured isolates and clinical material. Methods: Primers specific to the H ducreyi 16s rRNA gene were synthesised. PCR conditions were optimised and products were verified by restriction endonuclease digestion and agarose gel electrophoresis. Results: The method was able to detect all 28 H ducreyi strains tested; specificity was demonstrated using lysates of 12 related organisms. Applied to clinical samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The PCRs targeting herpesvirus were positive in 23 of 26 tested individuals (Table 1): 19 clinically affected (17 of those PCR positive for T pallidum) and 7 clinically nonaffected (2 of those PCR positive for T pallidum). The PCRs revealed a variety of sequences, ranging from only 1 animal infected with 16S rRNA AAC GCG AAG AAC CTT ACC TG 56 GAC GGG CGG TGT GTA C Klebsiella granulomatis 8 phoE CTA TGA CAG CAA GGA TGG CGA/ 58 CAG ACC GAA GTC GAA CTG ATA CTG Haemophilus ducreyi 6,40,42 16S rRNA CAA GTC GAA CGG TAG CAC GAA G/ 58 TCA TCT CTG AGT TCT TCT ATG 16S rRNA (nested) 6 TTC TGT GAC TAA CGT CAA TCA ATT TTG/ 58 TCG GAT TAA AGG GTG GGA CCT T Pan-herpesvirus 13 dPol GCG GCC GAT GGT CGT GAC Treponema pallidum tpF1 (tp1038) 39 GAA AAA AAT ACC ACA GCA CCG C/ 57 CAA TGC CGT AGA TGT GCC AGT G tpF1 (tp1038) (nested) 39 CGT GCC ATT GCT GCT ATC T/ 56 TGC CGT AGA TGT GCC AGT G gpd (tp0257/glpQ) 7 AAG AAC TTT CCC TCC TCC GTG C/ 55 CGT TTG ATA CGC TTC AGC TCG/ gpd (tp0257/glpQ) (nested) 7 GTG GGT TGG AAC AGA CAA CC/ 55 CGT TTG CAC ATA CAC TAG ATC C deoD (tp0170/pfs) 10 GGT TAC CAG AAA GGG CGT ATT CC/ 55 CGA CCA TTA CAC GAC CAT C deoD (tp0170/pfs) (nested) 10 TAA TGG CGT CCC CTT TGT TA/ 55 GAA GCC ACT ACC GAT GTG C tprl 25 CGT CAC CCT CTC CTG GTA GT 60 ATC CCT CGC CTG TAA ACT GA tprl (nested) 25 GTG AGA GGA GGG GGA GTG A 55 CAC CAT TGG AAA GGA AGG AG polA 33 CGT CTG GTC GAT GTG CAA ATG AGT G/ 65 TGC ACA TGT ACA CTG AGT TGA CTC GG polA 31,32 AGG ATC CGG CAT ATG TCC AA/ 60 GTG AGC GTC TCA TCA TTC CAA A 6FAM-ATG CAC CAG CTT CGA-BBQ (probe) Human (housekeeping gene) c-myc 23 GCC AGA GGA GGA ACG AGC T/ 60 GGG CCT TTT CAT TGT TTT CCA 6FAM-TGC CCT GCG TGA CCA GAT CC-BBQ (probe) I, inosine. cercopithecine herpesvirus 16 (herpesvirus papio 2, case No.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The PCRs targeting herpesvirus were positive in 23 of 26 tested individuals (Table 1): 19 clinically affected (17 of those PCR positive for T pallidum) and 7 clinically nonaffected (2 of those PCR positive for T pallidum). The PCRs revealed a variety of sequences, ranging from only 1 animal infected with 16S rRNA AAC GCG AAG AAC CTT ACC TG 56 GAC GGG CGG TGT GTA C Klebsiella granulomatis 8 phoE CTA TGA CAG CAA GGA TGG CGA/ 58 CAG ACC GAA GTC GAA CTG ATA CTG Haemophilus ducreyi 6,40,42 16S rRNA CAA GTC GAA CGG TAG CAC GAA G/ 58 TCA TCT CTG AGT TCT TCT ATG 16S rRNA (nested) 6 TTC TGT GAC TAA CGT CAA TCA ATT TTG/ 58 TCG GAT TAA AGG GTG GGA CCT T Pan-herpesvirus 13 dPol GCG GCC GAT GGT CGT GAC Treponema pallidum tpF1 (tp1038) 39 GAA AAA AAT ACC ACA GCA CCG C/ 57 CAA TGC CGT AGA TGT GCC AGT G tpF1 (tp1038) (nested) 39 CGT GCC ATT GCT GCT ATC T/ 56 TGC CGT AGA TGT GCC AGT G gpd (tp0257/glpQ) 7 AAG AAC TTT CCC TCC TCC GTG C/ 55 CGT TTG ATA CGC TTC AGC TCG/ gpd (tp0257/glpQ) (nested) 7 GTG GGT TGG AAC AGA CAA CC/ 55 CGT TTG CAC ATA CAC TAG ATC C deoD (tp0170/pfs) 10 GGT TAC CAG AAA GGG CGT ATT CC/ 55 CGA CCA TTA CAC GAC CAT C deoD (tp0170/pfs) (nested) 10 TAA TGG CGT CCC CTT TGT TA/ 55 GAA GCC ACT ACC GAT GTG C tprl 25 CGT CAC CCT CTC CTG GTA GT 60 ATC CCT CGC CTG TAA ACT GA tprl (nested) 25 GTG AGA GGA GGG GGA GTG A 55 CAC CAT TGG AAA GGA AGG AG polA 33 CGT CTG GTC GAT GTG CAA ATG AGT G/ 65 TGC ACA TGT ACA CTG AGT TGA CTC GG polA 31,32 AGG ATC CGG CAT ATG TCC AA/ 60 GTG AGC GTC TCA TCA TTC CAA A 6FAM-ATG CAC CAG CTT CGA-BBQ (probe) Human (housekeeping gene) c-myc 23 GCC AGA GGA GGA ACG AGC T/ 60 GGG CCT TTT CAT TGT TTT CCA 6FAM-TGC CCT GCG TGA CCA GAT CC-BBQ (probe) I, inosine. cercopithecine herpesvirus 16 (herpesvirus papio 2, case No.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The primers for H. ducreyi are located in the 16S rRNA gene and have, in part, been published (18,20). Outer primers, with a fragment length of 960 bp, were HD07 (5Ј CAA.GTC.GAA.CGG.TAG.CAC.GAA.G) and HD roe2 (5Ј TCA.TCT .CTG.AGT.TCT.TCT.ATG).…”
Section: Methodsmentioning
confidence: 99%
“…Studies using panels of unrelated bacterial, fungal, and viral DNA showed that these assays seemed to specifically amplify or detect H. ducreyi-specific sequences. The performance of these assays has been determined by using men with a clinical diagnosis of chancroid [49,50,52], men with GUD [51], or consecutive patients (men alone or men and women) with GUD [43••,44-48,50]. The results of these studies are summarized in Table 3.…”
Section: Chancroidmentioning
confidence: 99%